A case of Eagle syndrome with a marked elongation of the styloid process; investigating its relation to ankylotic spondylitis. Issue 2 (24th February 2023) - Angelou, Dimitrios; Hope, Nicholas; Canning, John; Stewart, Rosemary
Abstract: Eagle syndrome is characterized by the presence of an abnormally elongated styloid process and has been related to different etiologies, including enthesitis, a known feature of spondyloarthropathies. We are describing a case of marked elongation of the styloid process in a patient with pre‐existing ankylosing spondylitis and associated enthesopathy. Abstract : This is a rare case where a strong relation of Eagle syndrome to an etiologic factor like ankylotic spondylitis is demonstrated. This serves in reminding clinicians about the importance of not characterizing Eagle syndrome as idiopathic by default.